A Generalization of Chio’s Condensation Method - Any Muanalifah; Yuli Sagita; Nurwan Nurwan; Aini Fitriyah; Rosalio Artes Jr (Pattimura International Journal of Mathematics (PIJMath), 2024)
The Chio condensation method is a method to compute the determinant of a matrix A where by reducing the order of the matrix to a matrix. In this paper, we will generalize the condition where can be equal to zero. To compute the determinant, we can choose any element of matrix A that is not equal to zero as a pivot element.